Effects Of 0.25 % Mo (Molybdenum) Which Is Contained In The Ductile Cast Iron On Mechanical Properties Of Austempered Ductile Iron (ADI). - Nukman, Nukman; Arifin, Bustanul; Sugiarto, Bambang (UI Scholars Hub, 2002)
The aim of this research is to investigate the effects of 0.25 % Mo (Molybdenum) which is contained in the ductile cast iron on mechanical properties of Austempered Ductile Iron (ADI). The various temperatures and the holding times are used in the heat treatment processes. Using a given 0.25 % Mo in the ductile iron, ADI's alloyed developes a higher ultimate tensile stress value and decreases the elongation if we compare with the as cast (non alloy ductile iron). The higher impact energy value obtained at 9000 C austenization and 375o C austempering temperatures during 60 minutes holding times. The structure changes into ausferrit.